2002
DOI: 10.1021/es0200701
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Heavy Metal Speciation over Redox Gradients in Natural Water−Sediment Interfaces and Implications for Uptake by Benthic Organisms

Abstract: The sediment or fauna incubation experiment (SOFIE) is an experimental research tool that was developed to analyze concentrations and chemical speciation of heavy metals in pore waters of natural, undisturbed sediments or water-sediment interfaces over time, while simultaneously conducting exposure tests with sediment-dwelling organisms. In this way, concentrations of chemical species are directly linked to accumulation by biota. It is shown that discrete gradients of redox-sensitive metals and nutrients occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 24 publications
1
50
0
Order By: Relevance
“…Cooper et al (2000), who studied the formation of mineral phases during reduction, stated that microbial reduction of Fe(III) was inhibited when NO 3 − was present as an alternative electron acceptor. In this study, denitrification and Mn(IV) and Fe(III) reduction occurred simultaneously, and even simultaneous Fe(III) and SO 4 2− reduction was reported earlier (Postma and Jakobsen 1996;Vink 2002). Francis and Dodge (1990) showed that the release of metals from Fe-oxyhydroxides was facilitated by microbial action, and that dissolved Mn(II) facilitated this mechanism (Guha et al 2001).…”
Section: Floodplain Soil Reductionsupporting
confidence: 69%
See 3 more Smart Citations
“…Cooper et al (2000), who studied the formation of mineral phases during reduction, stated that microbial reduction of Fe(III) was inhibited when NO 3 − was present as an alternative electron acceptor. In this study, denitrification and Mn(IV) and Fe(III) reduction occurred simultaneously, and even simultaneous Fe(III) and SO 4 2− reduction was reported earlier (Postma and Jakobsen 1996;Vink 2002). Francis and Dodge (1990) showed that the release of metals from Fe-oxyhydroxides was facilitated by microbial action, and that dissolved Mn(II) facilitated this mechanism (Guha et al 2001).…”
Section: Floodplain Soil Reductionsupporting
confidence: 69%
“…The top 0.05-0.35 m was sampled in an undisturbed manner using SOFIE® cells (Sediment or Fauna Incubation Experiment), described in detail by Vink (2002). These cells enable undisturbed sampling, and accurate probing of pore water over time, while the redox status maintains intact.…”
Section: Floodplain Soil Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, this modeling framework defines bioavailability of TM. Dissolved TM exists in solution partially as free TM ion [89,90]. This species is hypothesized to be the bioavailable species in more simplified versions of the free ion activity model of toxicity.…”
Section: Risks Assessment In Aquatic Environmentsmentioning
confidence: 99%